Avaliação de silagens de cereais de inverno com diferentes estratégias de manejo - Silveira, Álisson Minozzo da (2017)
This research was conducted for evaluating the productivity, nutritional value and fermentative characteristics of winter cereal silages submitted or not to harvest in the Depressão Central do Rio Grande do Sul. So, experimental pastures were established in May 2013, and the treatments were composed by two varieties of white oats (Avena sativa L. cv. UPF 18 and cv. IPR 126) and two of wheat (Triticum sativum L. cv. BRS Tarumã and BRS Umbu), in two management conditions (half of the plots submitted to cuts during the cycle and the other half without cuts), totaling eight treatments, with four replications, in a completely randomized experimental design. Silage was made at the paste grain stage with approximately 30 to 35% dry matter, and after 60 days of fermentation, were opened for evaluation. To evaluate the level of nitrogen fertilization of winter cereal through the critical curve of nitrogen dilution by DM accumulation, five samples were taken per plot, every 21 days from te moment when the forage presented more of one tonne of dry matter per hectare. We used the model of N dilution in plant tissue, proposed by Lemaire and Salette (1984). The UPF 18 oats present higher productivity, with lower protein levels. IPR 126 oats have better nutritional characteristics such as NDFap, NFC and TDN. Fermentative characteristics of different studied silages are similar. As for the in vitro degradability parameters of the silages, wheat cultivars obtained higher gas production and CH4, showing to be more degradable than oats. The UPF 18 oat cultivar presented a lower concentration of SCFA. BRS Umbu wheat presented lower production of propionic acid, thus increasing the C2/C3 ratio. Nitrogen nutrition was deficient in all cultivars and developmental stages, and BRS Umbu wheat pasture was the one that most approached the model in relation to the others in the initial and intermediate phases of the cycle, with a higher NNI, but it was also the hich presented more nitrogen dilution during the cycle. IPR 126 oats had the lowest dilution of nitrogen over time. UPF 18 oats was more productive, however, IPR 126 oats presented best nutritional characteristics. wheat cultivars silage and IPR 126 oats are more digestible than the UPF 18 oats silage. Evaluated pastures presented nitrogen fertilization deficiency in all cultivars and developmental stages.